PENINGKATAN KREATIVITAS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN PROJECT BASED LEARNING TEMA 6 KELAS III SEKOLAH DASAR - Fahira Anatasya Hazri Handaka; Ratih Purnamasari; Maya Krisna Sushanty (Universitas Negeri Surabaya, 2023)
This research was compiled with the aim of increasing the creativity of students by applying the Project Based Learning learning model to class IIIA students at SDN Semeru 1 Bogor. Creativity referred to in this study include; have curiosity, self-confidence, persistence, and high imagination and dare to express opinions. This type of research is Collaborative Classroom Action Research (PTKK), a type of research that examines learning problems in the classroom through reflection in an effort to find problems with various planned actions. The research design uses the Kemmis and Mc. Taggart. This research was conducted in the even semester of the 2022/2023 school year, in February. The subjects of this study were class IIIA students at SDN Semeru 1 consisting of 28 students. The object of research is the creativity of students. Data collection techniques using observation and interviews. Data were analyzed descriptively and presented in the form of tables and graphs. The results showed that there was an increase in students' creativity, namely in the first cycle of 69% (high), then in the second cycle it increased to 90% (very high). This means an increase of 21%. Thus the use of the Project Based Learning learning model in Theme 6, especially in the SBdP content of Decorative Works material can increase the creativity of class IIIA students at SDN Semeru I.